Electrochemical device and electronic device
By using silicon carbon anode material containing B, P or S elements and electrolyte components such as fluorovinyl carbonate in lithium-ion batteries, a passivation layer is solved, and the problem of poor battery circulation performance caused by the active reaction of lithium silicon alloy is solved. Improves the battery's circulation performance and energy density.
Patent Information
- Application Number
- CN202411214633.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-17
AI Technical Summary
The lithium-silicon alloy formed by the lithiation of silicon-based materials in lithium-ion batteries is highly reactive and reactive, resulting in rapid consumption of electrolyte and loss of active lithium, which in turn affects the cycling performance of the battery.
Use silicon carbon anode material containing B, P or S elements, and add fluorovinyl carbonate and specific compounds to the electrolyte to form an interface passivation layer of lithium-containing inorganic compounds rich in S and F elements to prevent fluorocarbonic acid. The overpolymerization of vinyl ester coordinates to form a thinner SEI/cathode electrolyte interface layer, improving battery interface performance and cycling performance.
It effectively suppresses the side reaction between silicon and electrolyte, extends the service life of lithium-ion batteries, improves cycling performance and energy density, and avoids obstruction of ion transmission at the battery interface.
Smart Images

Figure CN119153786A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemistry, and in particular to an electrochemical device and an electronic device. Background Art
[0002] With the rapid development of electronic products, lithium-ion batteries are widely used in mobile phones, laptops, tablets, drones, electric vehicles, power tools, power storage systems, etc. due to their advantages such as high energy density, miniaturization and lightweight. Especially in the field of 3C products, consumer users still have great demand for improving the battery life of electronic products, so higher requirements are placed on the energy density of lithium-ion batteries. In order to further improve the energy density of lithium-ion batteries, high specific capacity electrode materials are required. Silicon-based materials, as a type of alloyed negative electrode material, can provide an ultra-high specific capacity of up to 4200mAh / g, so silicon-based materials are materials with great potential for improving energy density. However, after silicon-based materials are lithiated, lithium-silicon alloys will be formed. Lithium-silicon alloys have highly active reactivity and are extremely easy to attack solvent molecules in the electrolyte, resulting in rapid consumption of the electrolyte and loss of active lithium, so there will be problems with poor cycle performance. Summary of the invention
[0003] The purpose of this application is to provide an electrochemical device and an electronic device to improve the cycle performance of the electrochemical device. The specific technical solution is as follows:
[0004] The first aspect of the present application provides an electrochemical device, which includes a negative electrode plate and an electrolyte, wherein the negative electrode plate includes a negative electrode material layer, and the negative electrode material layer includes a silicon-carbon negative electrode material;
[0005] The silicon-carbon negative electrode material includes a miscellaneous element, the miscellaneous element includes at least one of B, P or S elements, and the mass percentage of the miscellaneous element is 0.1% to 2% based on the total mass of the silicon-carbon negative electrode material;
[0006] The electrolyte comprises a compound of formula I and fluoroethylene carbonate;
[0007]
[0008] wherein R is selected from fluorine-containing substituted or unsubstituted C2 to C6 alkyl, fluorine-containing substituted or unsubstituted C6 to C 12 The aryl group may be fully substituted or partially substituted with fluorine.
[0009] In one embodiment of the present application, based on the total mass of the negative electrode material layer, the mass percentage of silicon element is 15% to 40%.
[0010] In one embodiment of the present application, based on the total mass of the negative electrode material layer, the mass percentage of silicon element is 30% to 85%.
[0011] In one embodiment of the present application, the compound of formula I includes at least one of the following compounds:
[0012]
[0013]
[0014] In one embodiment of the present application, based on the total mass of the electrolyte, the mass percentage of the compound of formula I is 3% to 50%, preferably 3% to 20%.
[0015] In one embodiment of the present application, based on the total mass of the electrolyte, the mass percentage of fluoroethylene carbonate is 5% to 30%, preferably 5% to 15%.
[0016] In one embodiment of the present application, the electrolyte includes a nitrile compound, and the nitrile compound includes at least one of succinonitrile, adiponitrile, 1,3,6-hexanetrinitrile, glutaronitrile, methylglutaronitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile or sebacate, and the mass percentage of the nitrile compound is 0.1% to 5% based on the total mass of the electrolyte.
[0017] In one embodiment of the present application, the electrolyte further comprises a first component, the first component comprising at least one of dimethyl carbonate or diethyl carbonate; based on the total mass of the electrolyte, the mass percentage of the first component is 5% to 35%.
[0018] In one embodiment of the present application, the electrolyte also includes a second component, which includes at least one of ethyl acetate, propyl acetate, propyl propionate, butyl acetate, ethyl butyrate or ethyl isobutyrate; based on the total mass of the electrolyte, the mass percentage of the second component is 5% to 35%.
[0019] A second aspect of the present application provides an electronic device, which includes the electrochemical device described in the first aspect of the present application.
[0020] Beneficial effects of this application:
[0021] The present application provides an electrochemical device and an electronic device. The electrochemical device includes a negative electrode plate and an electrolyte, the electrolyte includes a compound of formula I and fluoroethylene carbonate (FEC), the negative electrode plate includes a negative electrode material layer, the negative electrode material layer includes a silicon-carbon negative electrode material, the silicon-carbon negative electrode material includes a heteroelement, and the heteroelement includes at least one of B, P or S elements, wherein the silicon-carbon negative electrode material is an excellent high-capacity negative electrode material, and the heteroelement coated on its surface can inhibit the side reaction of silicon with the electrolyte to a certain extent, but in the long cycle process, silicon will still contact with the electrolyte to produce a side reaction, resulting in the continuous generation of a solid electrolyte interface (SEI) film, which consumes the active lithium element in the battery. Fluorinated ethylene carbonate is a good electrolyte additive for electrochemical devices. Fluorinated ethylene carbonate in the electrolyte can form a cross-linked, highly tough polymer protective layer at the electrode interface during the battery formation process, thereby greatly improving the cycle performance of the electrochemical device. However, the consumption rate of fluoroethylene carbonate in the battery is relatively fast, and the formed polymer layer is relatively thick, which will hinder the transmission of lithium ions to a certain extent. The addition of the compound of formula I can form a positive and negative electrode interface passivation layer of a lithium-containing inorganic compound rich in S and F elements at the electrode interface, thereby preventing excessive polymerization of FEC, thereby synergistically forming a thinner SEI / cathode electrolyte interface (CEI) layer, improving the battery interface performance while improving the cycle performance.
[0022] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0024] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.
[0025] FEC (Fluoro Ethylene Carbonate) is an excellent film-forming additive used to repair the damage of SEI (Solid Electrolyte Interface) film on the surface of silicon particles, but the consumption rate of FEC is relatively fast, and excessive addition of FEC will lead to poor cycle performance of lithium-ion batteries. Therefore, the present invention forms an interface film rich in inorganic substances such as LiF and Li2S on the surfaces of positive and negative electrodes by adding a substance containing a -SO2F- group, thereby reducing the damage of SEI film on the surface of silicon particles and the damage of CEI (Chemical Elctrochemical Interface) film on the surface of the positive electrode, reducing the consumption of FEC and electrolyte solvent, and thus improving the long-term cycle stability of the battery.
[0026] The first aspect of the present application provides an electrochemical device, which includes a negative electrode plate and an electrolyte, wherein the negative electrode plate includes a negative electrode material layer, and the negative electrode material layer includes a silicon-carbon negative electrode material;
[0027] The silicon-carbon negative electrode material includes a silicon-carbon composite, and the silicon-carbon composite includes a heteroelement, the heteroelement includes at least one of B, P or S elements, and the mass percentage of the heteroelement is 0.1% to 2% based on the total mass of the silicon-carbon negative electrode material; for example, based on the total mass of the silicon-carbon negative electrode material, the mass percentage of the heteroelement can be 0.1%, 0.2%, 0.3%, 0.5%, 1.0%, 1.5%, 2.0% or a range consisting of any two of the values. Without being limited to any theory, the inventors of the present application have found that when the surface of the silicon-carbon negative electrode material is coated with heteroelement and the mass percentage of the heteroelement is 0.1% to 2%, it is beneficial to improve the transmission efficiency of lithium ions of the silicon-carbon composite at high rates, thereby further improving the cycle performance of the lithium-ion battery.
[0028] The electrolyte comprises a compound of formula I and fluoroethylene carbonate;
[0029]
[0030] wherein R is selected from fluorine-containing substituted or unsubstituted C2 to C6 alkyl, fluorine-containing substituted or unsubstituted C6 to C 12Aryl, fluorine substitution can be full substitution or partial substitution. Without being limited to any theory, the inventors of the present application have found that fluoroethylene carbonate is a good negative electrode surface film-forming additive, but the oxidation stability on the positive electrode side is insufficient. When fluoroethylene carbonate is used in combination with the compound of formula I, a passivation layer can be formed on the positive electrode surface, which not only retains the good negative electrode surface film-forming properties of fluoroethylene carbonate, but also reduces the oxidative decomposition of fluoroethylene carbonate at the positive electrode interface. The combination of the compound of formula I and fluoroethylene carbonate makes the lithium ion battery have a higher cycle capacity retention rate, thereby improving the cycle performance of the lithium ion battery.
[0031] In one embodiment of the present application, the impurity element is introduced by coating the surface of the silicon-carbon negative electrode material with an inorganic material, wherein the inorganic material includes B2O3, Na5P3O 10 Or at least one of Li2S.
[0032] In one embodiment of the present application, based on the total mass of the negative electrode material layer, the mass percentage of silicon element is 15% to 40%. For example, based on the total mass of the negative electrode material layer, the mass percentage of silicon element can be 15%, 20%, 25%, 30%, 35%, 40% or a range consisting of any two values therein, and the silicon element is introduced by the silicon-carbon negative electrode material, and the mass percentage of silicon element is adjusted by adding the amount of silicon-carbon negative electrode material in the preparation of the negative electrode sheet. Without being limited to any theory, the inventors of the present application have found that when the mass percentage of silicon element is 15% to 40%, the high energy density of silicon element can be brought into play, and at the same time, at this ratio, it is more conducive to extending the service life of the lithium-ion battery, thereby improving the comprehensive performance of the lithium-ion battery.
[0033] In one embodiment of the present application, based on the total mass of the negative electrode material layer, the mass percentage of the silicon-carbon negative electrode material is 30% to 85%. The mass percentage of the silicon-carbon negative electrode material can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or a range consisting of any two of the values. Without being limited to any theory, the inventors of the present application have found that when the mass percentage of the silicon-carbon negative electrode material is 30% to 85%, the high energy density of the silicon-carbon negative electrode material can be brought into play, which is beneficial to improving the energy density of the lithium-ion battery and will not cause performance degradation caused by excessive silicon-carbon material.
[0034] The negative electrode material layer of the present application may also include carbon material, which may be selected from at least one of natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon or soft carbon. Based on the total mass of the negative electrode material layer, the content of the carbon material may range from 15% to 70%.
[0035] In one embodiment of the present application, the compound of formula I comprises at least one of the following compounds:
[0036]
[0037]
[0038]
[0039] In one embodiment of the present application, the compound of formula I can be prepared by methods known in the art, or can be purchased through commercial channels.
[0040] In one embodiment of the present application, based on the total mass of the electrolyte, the mass percentage of the compound of formula I is 3% to 50%, preferably 3% to 20%. For example, the mass percentage of the compound of formula I can be 3%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range consisting of any two of the values. Without being limited to any theory, by controlling the mass percentage of the compound of formula I within 3% to 50%, it can be combined with FEC to produce a passivation interface on the electrode surface, which is beneficial to improve the cycle performance of the lithium ion battery.
[0041] In one embodiment of the present application, the electrolyte includes fluoroethylene carbonate, and the mass percentage of fluoroethylene carbonate is 5% to 30%, preferably 5% to 15%, based on the total mass of the electrolyte. For example, the mass percentage of fluoroethylene carbonate can be 5%, 10%, 15%, 20%, 25%, 30% or a range consisting of any two of the values. Without being limited to any theory, by controlling the mass percentage of fluoroethylene carbonate within 5% to 40%, it is beneficial for FEC to form a complete SEI film layer, improve the cycle performance of the lithium-ion battery, and at the same time will not lead to the formation of an overly thick SEI film layer, resulting in obstruction of interfacial ion transmission, resulting in a decrease in the low temperature and rate discharge effect of the battery. And it will not cause FEC to excessively decompose on the positive electrode side and produce a large amount of gas, which can balance the cycle stability.
[0042] In one embodiment of the present application, the electrolyte includes a nitrile compound, and the nitrile compound includes at least one of succinonitrile, adiponitrile, 1,3,6-hexanetrinitrile, glutaronitrile, methylglutaronitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile or sebacate, and the mass percentage of the nitrile compound is 0.1% to 5% based on the total mass of the electrolyte. For example, the mass percentage of the nitrile compound can be 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0% or a range consisting of any two of the values. Without being limited to any theory, nitrile compounds can effectively stabilize transition metal elements, thereby improving the stability of the positive electrode interface and improving the cycle performance of lithium-ion batteries.
[0043] In one embodiment of the present application, the electrolyte further comprises a first component, the first component comprising at least one of dimethyl carbonate or diethyl carbonate; based on the total mass of the electrolyte, the mass percentage of the first component is 5% to 35%. For example, the mass percentage of the first component can be 5%, 10%, 15%, 20%, 25%, 30%, 35% or a range consisting of any two of the values. Without being limited to any theory, dimethyl carbonate and diethyl carbonate have low viscosities, which are beneficial to reducing the viscosity of the electrolyte and the bulk impedance of the electrolyte, improving the ion transport capacity of the electrolyte, and introducing the electrolyte simultaneously with the compound of formula I to further improve the cycle performance of the lithium ion battery.
[0044] In one embodiment of the present application, the electrolyte further comprises a second component, the second component comprising at least one of ethyl acetate, propyl acetate, propyl propionate, butyl acetate, ethyl butyrate or ethyl isobutyrate; based on the total mass of the electrolyte, the mass percentage of the second component is 5% to 35%. For example, the mass percentage of the second component can be 5%, 10%, 15%, 20%, 25%, 30%, 35% or a range consisting of any two of the values. Without being limited to any theory, the second component has a lower viscosity, which is beneficial to reduce the viscosity of the electrolyte and the bulk impedance of the electrolyte, improve the ion transport capacity of the electrolyte, and introduce the electrolyte simultaneously with the compound of formula I to further improve the cycle performance of the lithium ion battery.
[0045] In the present application, the electrolyte also includes a lithium salt, and the lithium salt is not particularly limited. Any lithium salt known in the art can be used as long as the purpose of the present application can be achieved. For example, the lithium salt can be selected from at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3 and LiPO2F2. For example, LiPF6 can be selected as the lithium salt. Based on the mass of the electrolyte, the mass percentage of the lithium salt can be 8% to 20%, for example, the mass percentage of the lithium salt can be 8%, 10%, 12%, 13%, 15%, 18%, 20% or a range consisting of any two of the values.
[0046] The present application has no particular limitation on the non-aqueous solvent as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.
[0047] The carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The linear carbonate compound may include but is not limited to at least one of dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or methyl ethyl carbonate (MEC). The cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). Fluorinated carbonate compounds may include but are not limited to at least one of 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include but is not limited to at least one of methyl formate, methyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolactone, valerolactone or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.
[0048] The present application has no particular limitation on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of the non-aqueous solvent is 0% to 73.9%.
[0049] In one embodiment of the present application, the mass percentage of the silicon-carbon negative electrode material is 30% to 85% based on the total mass of the negative electrode material layer. The mass percentage of the silicon-carbon negative electrode material can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or any range therebetween. Without being limited to any theory, the inventors of the present application have found that when the mass percentage of the silicon-carbon negative electrode material is 30% to 85%, it can give play to the high energy density of the silicon element, which is beneficial to improving the energy density of the lithium-ion battery, and will not cause performance degradation caused by excessive silicon-carbon material.
[0050] In the present application, the electrochemical device also includes a positive electrode plate, which includes a positive electrode collector and a positive electrode material layer disposed on at least one surface of the positive electrode collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode collector along its own thickness direction, or on two surfaces of the positive electrode collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the positive electrode collector, or it can be a partial area of the surface of the positive electrode collector. This application has no special restrictions, as long as the purpose of this application can be achieved.
[0051] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).
[0052] The positive electrode material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or at least one of lithium titanate.
[0053] The positive electrode material layer may also include a conductive agent and a binder. The present application has no particular restrictions on the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the mass ratio of the positive electrode active material, the conductive agent, and the binder in the positive electrode material layer. Those skilled in the art can select according to actual needs, as long as the purpose of the present application can be achieved.
[0054] The present application has no particular restrictions on the thickness of the positive electrode current collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, and the thickness of the single-sided positive electrode material layer is 30 μm to 120 μm.
[0055] Optionally, the positive electrode sheet may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited, and it can be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, for example, it can be at least one of the above conductive agent and the above binder.
[0056] In the present application, the electrochemical device also includes a diaphragm. The present application has no particular restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include, but is not limited to, polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) films), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of diaphragm may include at least one of a woven membrane, a nonwoven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0057] In some embodiments of the present application, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer may be a nonwoven fabric, a film or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0058] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0059] In some embodiments of the present application, the inorganic layer includes inorganic particles and a binder. The present application is not particularly limited to inorganic particles, such as inorganic particles can include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application is not particularly limited to binders, such as binders can be at least one of the above-mentioned binders. In some embodiments of the present application, the polymer layer includes polymers, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymers, polyacrylic acid, polyacrylates, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).
[0060] In some embodiments of the present application, the inorganic layer may also include a thickener and a wetting agent. The present application has no particular restriction on the types of the thickener and the wetting agent, as long as the purpose of the present application can be achieved. For example, the thickener may include but is not limited to at least one of sodium carboxymethyl cellulose or lithium carboxymethyl cellulose; the wetting agent may include but is not limited to at least one of dimethyl siloxane, sodium dodecyl sulfate, trialkyl phosphate, methyl decanoate, and lauryl acetate.
[0061] In the present application, there is no particular limitation on the thickness of the separator as long as the purpose of the present application can be achieved. For example, the thickness of the separator may be 4 μm to 30 μm.
[0062] In the present application, the electrochemical device also includes a negative electrode plate, which includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer is disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode current collector, or it can be a partial area of the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.
[0063] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector. For example, the composite current collector may be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc.
[0064] In some embodiments of the present application, the negative electrode material layer may further include a conductive agent, a binder and / or a thickener. The present application does not particularly limit the types of the conductive agent and the thickener, as long as the purpose of the present application can be achieved. For example, the conductive agent and the binder may be at least one of the above conductive agent and the above binder. The thickener may include but is not limited to at least one of sodium carboxymethyl cellulose or lithium carboxymethyl cellulose. The present application does not particularly limit the mass ratio of the negative electrode material, the conductive agent, the binder and the thickener in the negative electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.
[0065] The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided negative electrode material layer is 30 μm to 120 μm.
[0066] The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 15 μm.
[0067] The present application has no particular restrictions on the conductive agent, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole.
[0068] The present application has no particular limitation on the binder as long as the purpose of the present application can be achieved. For example, the binder may include but is not limited to at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber or polyvinylidene fluoride.
[0069] The electrochemical device also includes a housing for accommodating a positive electrode plate, a diaphragm, a negative electrode plate and an electrolyte, as well as other components known in the field of electrochemical devices, and this application does not limit the above-mentioned other components. This application does not particularly limit the housing, and it can be a housing known in the art, as long as the purpose of this application can be achieved. For example, the housing can be a hard shell housing or a flexible shell. The material of the hard shell housing can be metal, and this application does not limit the type of metal, and a metal hard shell housing known in the art can be used, as long as the purpose of this application can be achieved. The flexible housing can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0070] The preparation process of the electrochemical device of the present application is well known to those skilled in the art, and there is no particular limitation in the present application. For example, the preparation process of the electrochemical device may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly with a stacked structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.
[0071] A second aspect of the present application provides an electronic device, comprising the electrochemical device in any of the aforementioned embodiments of the present application.
[0072] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0073] Example
[0074] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0075] Test methods and equipment
[0076] Cycle performance test:
[0077] Place the lithium-ion battery in a 25°C constant temperature test box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge to 4.45V at a constant current of 0.5C, then charge at a constant voltage to a current of 0.025C, let it stand for 5 minutes, and discharge to 3.0V at a constant current of 0.5C, and record it as the initial discharge capacity C1. Cycle this step for 200 times, record the discharge capacity C2 after 200 cycles, and calculate the lithium-ion battery cycle capacity retention rate. Cycle capacity retention rate = C2 / C1×100%.
[0078] Cycle thickness growth rate
[0079] Charge at a constant current of 0.5C to 4.45V, then charge at a constant voltage to a current of 0.025C, let stand for 5 minutes, measure the thickness, and count it as the thickness of the battery when it is fully charged for the first time; use the same charge and discharge process as in the above-mentioned cycle capacity retention test, cycle 500 times, measure the thickness, and count it as the battery thickness after the 500th cycle.
[0080] The difference between the battery thickness after the 500th cycle and the thickness of the battery when it is fully charged for the first time is divided by the thickness of the battery when it is fully charged for the first time. The battery thickness is measured with a micrometer, and 5 measurements are taken at 5 different positions to take the average value, which is the cycle thickness growth rate. The smaller the cycle thickness growth rate, the better.
[0081] Test of B, P and S element content:
[0082] The mass percentage of B, P and S elements in the silicon-carbon negative electrode material was tested using an ICP (Inductively coupled plasma) analyzer.
[0083] Test of silicon mass percentage:
[0084] The lithium-ion battery discharged at 0.5C to 3.0V was disassembled, the negative electrode plate was removed, and it was soaked in dimethyl carbonate (DMC) for 20 minutes, and then rinsed with DMC and acetone in turn. The negative electrode plate was then placed in an oven and baked at 80°C for 12 hours to obtain the negative electrode plate. The negative electrode plate was dried at 100°C in a vacuum oven for 24 hours, and 1g of the powdered sample of the negative electrode material layer on the negative electrode plate was scraped off with a blade, and then the mass percentage of silicon element in the negative electrode material layer was tested using an ICP (Inductively coupled plasma) analyzer.
[0085] Example 1-1
[0086] (1) Preparation of positive electrode sheet
[0087] The positive electrode active material LiCoO2, the conductive agent Super-P, and the binder PVDF are mixed in a mass ratio of 96:2.0:2.0, and N-methylpyrrolidone (NMP) is added, and the mixture is stirred and mixed to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 70wt%; the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and dried at 120°C to obtain a positive electrode sheet coated with a positive electrode material layer with a thickness of 100μm on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Dry under vacuum conditions at 120°C, and then after cold pressing, cutting, and slitting, a positive electrode sheet with a specification of 74mm×867mm is obtained.
[0088] (2) Preparation of negative electrode sheet
[0089] The microporous carbon material with a carbon content of 50% is loaded with nano-silicon and an inorganic coating material, sodium tripolyphosphate Na5P3O 10 The mixture is added into an ethanol solvent to form a suspension, and ball milling is performed to mix and disperse the mixture evenly to obtain a mixture, and the mixture is filtered and dried to obtain a silicon-carbon negative electrode material whose surface is coated with an inorganic coating layer.
[0090] The silicon-carbon negative electrode material, artificial graphite, conductive agent Super-P, thickener CMC, and adhesive SBR prepared according to the above scheme were dissolved in solvent deionized water at a mass ratio of 50:46.5:1.0:1.0:1.5 and mixed evenly to form a negative electrode slurry. The negative electrode slurry was then evenly coated on the negative electrode current collector copper foil with a coating amount of 1.85 g / cm 2 , then dried at 85°C, cold pressed, trimmed, cut into pieces, and slit, and then dried at 110°C under vacuum conditions for 4 hours, and the negative electrode ears are welded to make negative electrode sheets that meet the requirements.
[0091] Among them, based on the total mass of the negative electrode material layer, the silicon element content is as shown in Table 1 below, and based on the total mass of the silicon-carbon negative electrode material, the impurity element content is as shown in Table 1 below.
[0092] (3) Preparation of electrolyte
[0093] In an argon atmosphere glove box with a water content of less than 10ppm, ethyl propionate, propylene carbonate and ethyl methyl carbonate are mixed in a ratio of 3:4:3 to obtain a basic solvent, and the compound of formula I-1, fluoroethylene carbonate and lithium salt LiPF6 are added, dissolved and mixed evenly to obtain an electrolyte; wherein, based on the total mass of the electrolyte, the mass percentage of lithium salt LiPF6 is 12.5%, the mass percentage of fluoroethylene carbonate is 20%, the mass percentage of the first compound formula I-1 is 25%, and the remainder is the basic solvent.
[0094] (4) Diaphragm
[0095] A porous polyethylene film with a thickness of 7 μm (provided by Shanghai Enjie Company) was used as the separator.
[0096] (5) Preparation of lithium-ion batteries
[0097] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, so that the separator is located between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound, the positive electrode ear is connected to the positive electrode sheet, and the negative electrode ear is connected to the negative electrode sheet to obtain an electrode assembly. The electrode assembly is placed in an aluminum foil packaging bag, and the positive electrode ear and the negative electrode ear are led out from the inner space of the aluminum foil packaging bag to the outer space of the aluminum foil packaging bag, and the moisture is removed at 80°C, and the electrolyte prepared above is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, formation, degassing, shaping and other processes.
[0098] Example 1-2 to Example 1-30
[0099] Except that the type of coated inorganic material, the mass percentage of impurity elements contained in the silicon-carbon negative electrode material, and the mass percentage of silicon element in the negative electrode material layer are adjusted according to Table 1 in the preparation of the negative electrode plate, and the type and mass percentage of the compound of formula I, the mass percentage of fluoroethylene carbonate, and the mass percentage of the basic solvent are adjusted according to Table 1 in the preparation of the electrolyte, and the mass percentage of the lithium salt LiPF6 remains unchanged, the rest is the same as Example 1-1.
[0100] Example 2-1 to Example 2-7
[0101] Except that nitrile compounds are added according to Table 2 in the preparation of the electrolyte, and the type and mass percentage of the nitrile compounds are adjusted, the mass percentage of the basic solvent is changed accordingly, and the mass percentage of the lithium salt LiPF6 remains unchanged, the rest is the same as Example 1-1.
[0102] Example 3-1 to Example 3-15
[0103] Except that the first component and the second component are added according to Table 3 in the preparation of the electrolyte, and the types and mass percentages of the first component and the second component are adjusted, and the mass percentage of the lithium salt LiPF6 remains unchanged, the rest is the same as the corresponding embodiment 2-3 in the table.
[0104] Comparative Example 1
[0105] Except that the compound of formula I is not added in the preparation of the electrolyte, the mass percentage of the basic solvent is changed accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as Example 1-1.
[0106] Comparative Example 2
[0107] Except that fluoroethylene carbonate is not added in the preparation of the electrolyte, the mass percentage of the base solvent is changed accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as Example 1-1.
[0108] Comparative Example 3
[0109] Except that the mass percentage of the compound of formula I in the preparation of the electrolyte is 1%, the mass percentage of fluoroethylene carbonate is 1%, the mass percentage of the base solvent is changed accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as Example 1-1.
[0110] Comparative Example 4
[0111] Except that the mass percentage of the compound of formula I in the preparation of the electrolyte is 1%, the mass percentage of fluoroethylene carbonate is 35%, the mass percentage of the base solvent is changed accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as Example 1-1.
[0112] Comparative Example 5
[0113] Except that the mass percentage of the compound of formula I in the preparation of the electrolyte is 55%, the mass percentage of fluoroethylene carbonate is 1%, the mass percentage of the base solvent changes accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as Example 1-1.
[0114] Comparative Example 6
[0115] Except that the silicon-carbon composite is not coated during the preparation of the negative electrode plate, the rest is the same as Example 1-1.
[0116] Table 1
[0117]
[0118]
[0119] It can be seen from Examples 1-1 to 1-30 and Comparative Examples 1 to 6 that when the type and mass percentage of the heteroelement, the type and mass percentage of the compound of Formula I, the mass percentage of fluoroethylene carbonate, and the mass percentage of silicon are within the scope of the present application, the lithium ion battery has a higher cycle capacity retention rate and a lower cycle thickness growth rate.
[0120] Table 2
[0121]
[0122] It can be seen from Example 1-1 and Example 2-1 to Example 2-7 that when the type and mass percentage of the nitrile compound are within the scope of the present application, the lithium-ion battery has a higher cycle capacity retention rate and a lower cycle thickness growth rate.
[0123] Table 3
[0124]
[0125]
[0126] It can be seen from Examples 2-3 and 3-1 to 3-15 that when the types and mass percentages of the first component and the second component are within the range of this application, the cycle capacity retention rate of the lithium-ion battery is higher and the cycle thickness growth rate is further reduced. When the first component and the second component are used in combination at the same time, the cycle capacity retention rate can be further improved.
[0127] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the scope of protection of the present application.
Claims
1. An electrochemical device comprising a negative electrode sheet and an electrolyte, wherein: The negative electrode plate comprises a negative electrode material layer, and the negative electrode material layer comprises a silicon-carbon negative electrode material; The silicon-carbon negative electrode material includes a heteroelement, wherein the heteroelement includes at least one of B, P or S elements, and the mass percentage of the heteroelement is 0.1% to 2% based on the total mass of the silicon-carbon negative electrode material; The electrolyte comprises a compound of formula I and fluoroethylene carbonate; wherein R is selected from fluorine-containing substituted or unsubstituted C2 to C6 alkyl, fluorine-containing substituted or unsubstituted C6 to C 12 Aryl.
2. The electrochemical device according to claim 1, wherein: Based on the total mass of the negative electrode material layer, the mass percentage of silicon element is 15% to 40%.
3. The electrochemical device according to claim 1, wherein Based on the total mass of the negative electrode material layer, the mass percentage of the silicon-carbon negative electrode material is 30% to 85%.
4. The electrochemical device according to claim 1, wherein The compound of formula I includes at least one of the following compounds:
5. The electrochemical device according to claim 1, wherein Based on the total mass of the electrolyte, the mass percentage of the compound of formula I is 3% to 50%.
6. The electrochemical device according to claim 1, wherein Based on the total mass of the electrolyte, the mass percentage of the compound of formula I is 3% to 20%.
7. The electrochemical device according to claim 1, wherein: Based on the total mass of the electrolyte, the mass percentage of the fluoroethylene carbonate is 5% to 30%.
8. The electrochemical device according to claim 1, wherein Based on the total mass of the electrolyte, the mass percentage of the fluoroethylene carbonate is 5% to 15%.
9. The electrochemical device according to any one of claims 1 to 8, wherein: The electrolyte includes nitrile compounds, and the nitrile compounds include at least one of succinonitrile, adiponitrile, 1,3,6-hexanetrinitrile, glutaronitrile, methylglutaronitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile or sebacate; based on the total mass of the electrolyte, the mass percentage of the nitrile compounds is 0.1% to 5%.
10. The electrochemical device according to any one of claims 1 to 8, wherein: The electrolyte further includes a first component, which includes at least one of dimethyl carbonate or diethyl carbonate; based on the total mass of the electrolyte, the mass percentage of the first component is 5% to 35%.
11. The electrochemical device according to any one of claims 1 to 8, wherein: The electrolyte also includes a second component, which includes at least one of ethyl acetate, propyl acetate, propyl propionate, butyl acetate, ethyl butyrate or ethyl isobutyrate; based on the total mass of the electrolyte, the mass percentage of the second component is 5% to 35%. 12 . An electronic device comprising the electrochemical device according to claim 1 .
Citation Information
Cited By
Electrochemical device and electronic device
WO2026045770A1
